Sound‐Insulation Performance of Polylactic Acid Parts 3D Printed by Fused Filament Fabrication with Functionally Graded Porous Structure for Effective Noise Reduction - Reza Navidpour; Taher Azdast; Rezgar Hasanzadeh; Milad Moradian; Peyman Mihankhah; Asghar Rasouli (Macromolecular Materials and Engineering, 2025)
Abstract The emergence of 3D printing technology has enabled the fabrication of absorbers with functionally graded (FG) porous structure and controlled porosity that can absorb sound waves across a broader frequency range. In this study, sound absorption properties of fused filament fabrication (FFF) 3D printed parts with FG porous structure and controlled pore sizes are investigated. For this purpose, samples with single porosity with infill densities of 40% to 90% are first printed to compare with the absorption coefficient of FG porous samples. FG porous samples are also printed as unified structures in two groups of FG porosity 40/50/60% and 70/80/90%. Sound absorption coefficient is tested using the transfer function method and impedance tube sound absorption test system. The experimental results of single porosity samples show that at higher frequencies, samples with lower infill density (higher porosity) have higher sound absorption coefficients, while at lower frequencies, samples with higher infill density (lower porosity) have more effective sound absorption. Unlike uniform porous structures at lower frequencies, FG porous structure provides higher sound absorption without increasing thickness and weight. In addition, it is found that the orientation of samples with the FG porous structure has a different behavior of the sound absorption coefficient.